Unpacking the root causes of gambling in the Asian community: Contesting the myth of the Asian gambling culture - Colby, Mia Han; Hires, Ben; Le, Lisette; Sauma, Dawn; Yau, Man Yoyo; Chu, MyDzung Thi; Rubin, Heang Leung (Frontiers in Public Health, 2022)
Introduction Problem gambling is a public health issue both in the United States and internationally and can lead to mental health and socioeconomic concerns for individuals, families, and communities. Large epidemiological studies on problem gambling have neglected to include working-class, immigrant Asian Americans, who are at higher risk for problem gambling. The lack of data on Asian American gambling may explain a subsequent lack of culturally and linguistically appropriate treatment and prevention services. Additionally, the invisibility of Asian American data in published literature has helped to perpetuate a commonly held myth of an Asian gambling culture. This stereotype of the “Asian gambler” is a form of anti-Asian racism which serves to ignore and minimize the root causes of problem gambling in the Asian American community. Methods Utilizing a community-based participatory research approach, 40 interviews were conducted with the local Khmer (n = 12), Chinese (n = 20), Korean (n = 3), and Vietnamese (n = 5) immigrant communities in the Greater Boston region to assess how problem gambling manifests in the local Asian community. Interviews were conducted in language by bilingual/bicultural community fieldworkers experienced in serving their respective communities. Flyers and social media were used to recruit participants. The interviews were coded into themes which provided a better understanding of the patterns of systemic issues contributing to problem gambling in the Asian American community. Results Interviewees provided insights into the underlying issues of poverty and social and cultural loss due to immigration as root causes for problem gambling in the Asian American community. The interviews indicate that many individuals in these Asian immigrant communities, who are striving to make a living off low-wage and stressful jobs, struggle to integrate into American society. They often lack culturally appropriate and accessible social and recreational activities, a void that casinos capitalize on through targeted behaviors. Discussion Research must address the social and structural barriers in the Asian American communities rather than relying on the “Asian gambler” stereotype and assuming interventions for a general American problem gambler will work for Asian immigrants. The research points to a need for gambling interventions and services that are centered on lived experiences.